A new species of Amphipoea Billberg, 1820, from northwestern Iran (Lepidoptera: Noctuidae) - Zahiri, Reza; Fibiger, Michael (Zootaxa, 2006)
Amphipoea maryamae, sp. n., is described from the low mountains of West Azerbaijan province in northwestern Iran. The habitat is semi-steppe with herbaceous vegetation and scattered trees. Adults and male and female genitalia are described and illustrated and compared with presumably closely related Amphipoea species. The genus Amphipoea previously was unrecorded from Iran.